Implementasi Program LKPM Online Di Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Surabaya - Dito Firmansyah Rosidi; Bambang Kusbandrijo (Journal of Research and Development on Public Policy, 2024)
Licensing services are one of the administrative services carried out by the government, as well as the Surabaya City Government through the One Stop Integrated Services and Investment Service (DPM-PTSP) which has even implemented a system Online Single Submission (OSS) so that the quality of service becomes better. This research aims to determine the effectiveness of the LKPM Online program in collecting NIB data on the OSS system at the Surabaya City One Stop Investment and Integrated Services Service. Program Online Single Submission (OSS) makes it easier for the government to register business actors in the city of Surabaya quickly, efficiently and transparently. The method used to carry out this research is descriptive research with a qualitative approach. This research was chosen because it presents data systematically, factually and accurately regarding the facts in the field. This research uses a descriptive research design with a qualitative approach aimed at exploring facts regarding the quality of public services in the field of business license administration. The research results show that the quality of service with the OSS-based LKPM Online program shows several supporting factors that must be improved in service delivery in order to realize the quality of administrative services in an agency in creating a community environment that is aware of the administration of business permits. This research recommendation aims to explain the effectiveness of the OSS-based Online LKPM program which can simplify the administration of business license numbers.